PENGARUH KINERJA KEUANGAN, DANA ALOKASI UMUM DAN SILPA PADA ALOKASI BELANJA MODAL - Rosadi, Ade Imron; Suputra, I Dewa Gede Dharma (E-Jurnal Akuntansi; Vol 19 No 2 (2017), 2017)
The purpose of this study to examine the effect of financial performance, general allocation fund, and SiLPA of the budget over the allocation of the capital expenditure budget in district/ cities in the province of Bali in 2010-2014. The sampling method used was saturated sampling technique. The sample in this study the Budget Realization Report number 45 districts/cities that covering 8 districts and 1 city in the study period 2010-2014. Data analysis method used is multiple linear regression analysis method. Based on the analysis found that across the independent variables affect the dependent variable. Financial performance in the form of the ratio of local independence significant and negative effect on capital expenditure for the district/city of Bali Province, the general allocation fund significant and positive effect on capital expenditure for the district/city of Bali province, and SiLPA significant and positive impact on the capital expenditure for the district / city of Bali Province.
Keywords: Financial Performance, General Allocation Fund, SiLPA, Capital Expenditure